DIFFERENTIAL SALT TECTONIC DEFORMATION AND SEGMENTATION OF THE KUQA FORELAND FOLD-THRUST BELT, TARIM BASIN, NORTHWEST CHINA - Tang L.; Yu Y.; Chen S.; Jingchang L.; Wang Q.; Yang W.; Xie H.; Peng G. (My University, 2006)
The differential salt tectonic deformation and segmentation in the Kuqa foreland fold-thrust belt have been observed by field observation, geographic information system (GIS) analysis, 3D visualization, salt-related structural styles, balanced cross section, and estimation of shortening strains and rates. The differential salt tectonic deformation is mainly represented by structural differentiation at different levels, and structural zonation and segmentation in transverse and longitudinal sections. The boundaries between the structural segments are mainly strike-slip faults or tear faults revealed by terminal facets, scratches, steps, misplaced hills and river valleys. The GIS analysis maybe indicates some characteristic details of structural segmentation. Several segments of buried residual salt pillows are revealed by 3D visualization. Distinct structural styles occur in different segments. The analysis of balanced cross section may estimate differential amounts and rates of shoretening in different segments. The origin of differential salt tectonic deformation and segmentation may be, on one hand, controlled by the segmentation of the Tianshan mountains, and the other, are related to the differential sedimentation and distribution of the salt beds, pre-exist faults and basement uplifts as well as paleotectonic ramps.
Keywords: DIFFERENTIAL STRUCTURAL DEFORMATION; KUQA FORELAND FOLD-THRUST BELT; SALT TECTONICS; SEGMENTATION; TARIM BASIN